Degradation Of High Concentrations Of 2-Chlorophenol And 2,6-Dichlorophenol By Mixed Anaerobic Culture - MUKESH GOEL,; K. RAVI KUMAR,; ASHUTOSH DAS,; M. SREEHARSHA, (International Journal of Pharma and Bio Sciences, 2012)
Effluents containing high concentrations of chlorophenols are biorecalcitrant and are difficult to degrade. It creates highly toxic and unfavorable environment for the growth and sustenance of all but the hardiest microbial species. Degradation of 2-chlorophenol (CP) and 2,6-dichlorophenol (DCP) using mixed anaerobic culture is studied in this paper. Glucose concentrations were varied to observe the effects of glucose concentration on the chlorophenols degradation. Three different glucose concentrations, 0.5, 1 and 2 g/l were taken for this study. The mixture of CP and DCP were also studied to assess the impact of individual compounds on their degradation. It was observed that degradation rate negligibly increased when glucose concentration was increased from 1 – 2 g/l. For the culture containing mixture of CP and DCP, CP showed faster degradation compared to DCP.